The key to 2,6-dichloro-1,4-benzoquinone reproductive toxicity and green tea detoxification: Covalent binding and competitive binding - Meixian Liu; Zhiyuan Ning; Yong Cheng; Zhiyuan Zheng; Xiaoxue Yang; Ting Zheng; Na Li; Jian-Lin Wu (Ecotoxicology and Environmental Safety)
Halobenzoquinones (HBQs) are ubiquitous disinfection by-products (DBPs) in chlorinated drinking water with various health risks including reproductive toxicity, while the potential mechanisms are still unclear. Although green tea exhibits common detoxifying properties, its ability to mitigate the toxicity of HBQs still needs to be further deepened and explored. This study attempted to investigate the possible mechanism of the most common HBQ, 2,6-dichloro-1,4-benzoquinone (2,6-DCBQ) induced reproductive toxicity and elucidate the protective effect of green tea using a series of liquid chromatography-tandem mass spectrometry (LC-MS) approaches. Firstly, in vivo experiments showed that 2,6-DCBQ could induce testicular damage in male rats via significantly decreasing sperm-associated Leydig cells and seminiferous tubules. Then, in vitro incubation of 2,6-DCBQ with amino acids suggested that 2,6-DCBQ could bind to proteins via residues of cysteine or lysine and provided five additional modification patterns. Following, proteomics analysis revealed that at least 42 proteins were modified by 2,6-DCBQ, which were mainly enriched in the reproductive system. These results highlighted the significance of covalent protein modification in 2,6-DCBQ reproductive toxicity. Fortunately, we found that catechins (a class of major components of green tea) could competitively bind to 2,6-DCBQ in vivo and in vitro, reducing the amount and type of 2,6-DCBQ-protein adducts, thereby attenuating the reproductive system damage caused by 2,6-DCBQ. This study provides new insights into 2,6-DCBQ-induced reproductive system damage and reveals a new mechanism of green tea detoxification. Moreover, these findings offer potential strategies for alleviating the harmful impacts of environmental toxicants on human health.